2017
DOI: 10.9767/bcrec.13.2.1382.245-255
|View full text |Cite
|
Sign up to set email alerts
|

Fe/Indonesian Natural Zeolite as Hydrodeoxygenation Catalyst in Green Diesel Production from Palm Oil

Abstract: The Petroleum diesel-based fossil fuel remains the primary source of energy consumption in Indonesia. The utilization of this unrenewable fuel depletes fossil fuels; thus, an alternative, renewable fuel, such as one based on biohydrocarbon from biomass-green diesel-could be an option. In this work, green diesel was produced through the hydrodeoxygenation from palm oil and processed in a batch-stirred autoclave reactor over natural zeolite (NZ) and NZ modified with 3 wt.% Fe metal (Fe/NZ) as heterogeneous catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
3
15
1
Order By: Relevance
“…The reductions in the peak intensities were comparable with the reduction in oxygen content in the product. 49 By comparing the deoxygenised liquid product, Ni 10 -Mg 10 /MWCNT and Ni 10 -Mn 10 /MWCNT showed signicant decreases in C]O intensity, suggesting higher deoxygenation activity. The absence of the C-O-C band at 1148 cm À1 indicated that a triglyceride ester bond was eliminated possibly to produce free fatty acids.…”
Section: Characterisation Of the Catalystsmentioning
confidence: 95%
“…The reductions in the peak intensities were comparable with the reduction in oxygen content in the product. 49 By comparing the deoxygenised liquid product, Ni 10 -Mg 10 /MWCNT and Ni 10 -Mn 10 /MWCNT showed signicant decreases in C]O intensity, suggesting higher deoxygenation activity. The absence of the C-O-C band at 1148 cm À1 indicated that a triglyceride ester bond was eliminated possibly to produce free fatty acids.…”
Section: Characterisation Of the Catalystsmentioning
confidence: 95%
“…Recent efforts have shifted away from converting lipid feedstocks to biodiesel (i.e., fatty acid methyl esters, FAMES) in favor of hydrocarbons with a composition similar to petroleum-derived diesel fuel (i.e., so-called “renewable diesel” or “green diesel”). This has most often been accomplished through catalytic hydrodeoxygenation (HDO) of the triacylglyceride structure at elevated temperatures and H 2 pressures (eq a–e): Green diesel is attractive due to its direct compatibility with petroleum diesel, allowing for full integration with existing refinery and transportation infrastructure. , Green diesel production by HDO has been demonstrated for a variety of lipid-rich terrestrial crops (e.g., peanuts and soybeans), , and there is growing interest in applying the process to inedible and waste lipid feedstocks (e.g., waste cooking oil, animal fat, algae lipids, nonedible vegetable oils). Widespread deployment of green diesel production by HDO has been limited by multiple challenges.…”
Section: Introductionmentioning
confidence: 99%
“…† The FTIR spectra of ceiba oil showed the main absorption bands at 2917 cm −1 and 2850 cm −1 (–CH stretching), 1740 cm −1 (–C O ester stretching), and 1120 cm −1 (C–O–C stretching). Based on an earlier work, 82 Putra et al proposed that the DO activity can be evaluated by comparing the decrease in the C O and C–O–C peak intensities. This is confirmed, as there is a slight shift of the C O peak at 1740 cm −1 in ceiba oil to 1702 cm −1 in the liquid products, indicating transformation of carboxylic acid from ester via triglyceride cracking.…”
Section: Resultsmentioning
confidence: 99%